Penerapan Model PBL Berbantuan Media Wordwall Untuk Meningkatkan Hasil Belajar IPAS Kelas IV SDN Rejosari 01 - Nabila Atika; Ngurah Ayu Nyoman Murniati (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2024)
This research aims to improve student learning outcomes by implementing the PBL model assisted by Wordwall media. Classroom Action Research (PTK) will be used in this type of research. The subjects of this research were 28 students in class IVC at SDN Rejosari 01 Semarang for the 2023/2024 academic year. Data collection techniques using observation techniques and tests. The object of this research is the learning results from the science content material I Am a Magical Object. This research will use quantitative and qualitative data. From research findings, it is possible that student learning outcomes will improve by using the Problem Based Learning model assisted by Wordwall. The learning results obtained during the pre-cycle were 46% learning completeness for 28 students. In cycle I, the completeness of student learning outcomes saw an increase of 71% for 28 students. Meanwhile, in cycle II, the completeness of students' learning outcomes experienced a significant increase of 89% from 28 students. Therefore, this research can be considered successful because it has met the criteria for completeness of learning outcomes between pre-cycle to cycle I and cycle II. Student learning outcomes are better, after implementing the Problem Based Learning model assisted by Wordwall.